2015
DOI: 10.1007/s10815-014-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

The risk of birth defects after assisted reproduction

Abstract: Purpose Aim of this study was to investigate the association between congenital malformations and type of conception (spontaneous or medically assisted). Methods This is a population based study using data from the regional data base of Lombardy, a Northern Italian Region with a population of about 10 million inhabitants. Included in the study were 277,043 neonates born in Lombardy during the study period 2010-2012. Adjusted and unadjusted odds ratios (OR), and corresponding 95 % confidence intervals (CI), of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 13 publications
(29 reference statements)
0
23
0
Order By: Relevance
“…Some meta-analyses have suggested that infants, both singletons and multiples, born following ART are at increased risk of perinatal complications and birth defects compared with spontaneous conceptions. [ 39 , 40 ] Meanwhile, the latest available review on the outcome of assisted reproduction concludes that some of the risks to infants born following ART do not arise as a result of the applied techniques or treatments but rather from the underlying health risks of being subfertile. [ 41 , 42 ] Therefore, subfertile couples should improve their health statuses before undergoing ART.…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses have suggested that infants, both singletons and multiples, born following ART are at increased risk of perinatal complications and birth defects compared with spontaneous conceptions. [ 39 , 40 ] Meanwhile, the latest available review on the outcome of assisted reproduction concludes that some of the risks to infants born following ART do not arise as a result of the applied techniques or treatments but rather from the underlying health risks of being subfertile. [ 41 , 42 ] Therefore, subfertile couples should improve their health statuses before undergoing ART.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, if blastocyst transfer, for example, proves to be a risk factor for MZT, the figure emerging from our analysis may change in the near future (data here refer to the period 2007-2011 when the blastocyst strategy was uncommon in our region). Fourth, as controls we referred to a population-based rate as estimated in a recent study of our group in the same geographical area (Parazzini et al, 2015). This choice presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45][46][47] However, it is not entirely clear if the contributing factor is the ART procedure, or the underlying infertility itself. One Italian study of >7000 infants born after ART or ovulation induction suggested the increased prevalence of birth defects associated with non-spontaneous conception was largely due to confounding factors such as maternal age, 48 which is associated with poorer oocyte quality, mitochondrial dysfunction, aneuploidy and epigenetic alteration. 49 A large Danish longitudinal study found singletons born of infertile couples who conceived naturally (time to pregnancy >12 months) or after infertility treatment including different types of ART or surgeries had a higher prevalence of congenital malformations compared with singletons born of fertile couples (time to pregnancy ⩽12 months).…”
Section: Birth Defects In Art Singleton Pregnanciesmentioning
confidence: 99%